Vejrforholdene i Landbrugsaaret 1908—09.(Fra 1. Oktober 1908 til 30. September 1909.) - Willaume-Jantzen, F. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1908—09.(Fra 1. Oktober 1908 til 30. September 1909.)